The construction sector in twenty European countries during the recession 2008–2009 – country ranking by MULTIMOORA - M. Brauers, Willem Karel; Kildienė, Simona; Zavadskas, Edmundas Kazimieras; Kaklauskas, Artūras (International Journal of Strategic Property Management, 2013)
The recession 2008-2009 which influenced the World economy has set new challenges for the development of the European construction sector. In the years 2008–2009 a great number of countries faced serious production and employment breakdowns. The purpose of this paper is to analyze the construction sector from a macroeconomic point of view by comparing construction market variations appeared during the crisis in twenty European countries. Therefore statistical indicators of the construction sector were used and a multiobjective evaluation method under the name of MULTIMOORA was employed. However these traditional indicators of the construction sector deliver an incomplete definition of real situations within the sector as during the recession plenty of constructed buildings remained unsold. Therefore the authors of this article propose a rather complex comparison of construction indicators for different European countries. The case study provides the analysis and calculations performed with the help of the MULTIMOORA method. This method enables the evaluation of European countries in accordance with the investigated objectives and ranges them into different groups according to the objectives set for the construction sector.First Publish Online: 3 Apr 2013